2013
DOI: 10.3727/096368912x639017
|View full text |Cite
|
Sign up to set email alerts
|

Human Adipose-Derived Stromal Cells for Cell-Based Therapies in the Treatment of Systemic Sclerosis

Abstract: The present study was designed to evaluate the clinical outcome of cell-based therapy with cultured adiposederived stromal cells (ASCs) for the treatment of cutaneous manifestations in patients affected by systemic sclerosis (SSc). ASCs have an extraordinary developmental plasticity, including the ability to undergo multilineage differentiation and self-renewal. Moreover, ASCs can be easily harvested from small volumes of liposuction aspirate, showing great in vitro viability and proliferation rate. Here we is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
95
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(102 citation statements)
references
References 63 publications
4
95
2
1
Order By: Relevance
“…A. Tyndall / Immunology Letters xxx (2015) xxx-xxx The authors concluded cautiously that MSC improved the acral ulcers and to a lesser extent the skin thickening, but that given the heterogeneity of the clinical manifestations, larger studies were required. Further reports and uncontrolled small series have also shown positive effects following the local injection of autologous adipose tissue derived MSC into face [28] and digits [29], autologous blood and bone marrow derived mononuclear cells [30] and IVI autologous bone marrow derived MSC [31] in SSc patients. No significant toxicity was reported.…”
Section: Systemic Sclerosismentioning
confidence: 90%
“…A. Tyndall / Immunology Letters xxx (2015) xxx-xxx The authors concluded cautiously that MSC improved the acral ulcers and to a lesser extent the skin thickening, but that given the heterogeneity of the clinical manifestations, larger studies were required. Further reports and uncontrolled small series have also shown positive effects following the local injection of autologous adipose tissue derived MSC into face [28] and digits [29], autologous blood and bone marrow derived mononuclear cells [30] and IVI autologous bone marrow derived MSC [31] in SSc patients. No significant toxicity was reported.…”
Section: Systemic Sclerosismentioning
confidence: 90%
“…In our previous studies on AD, hUCB-MSCs at passages 5 to 7 were used in both co-culture experiments and in vivo studies, and the clinical trial was conducted using hUCB-MSCs at passage 5. Additionally, Scuderi et al showed that SC injection of autologous AT-derived MSCs (AT-MSCs) with hyaluronic acid (HA) scaffold resulted in the significant improvement of skin symptoms in patients with SSc, and the number of passages for injected MSCs was between 2 and 3 [65]. …”
Section: Properties Of Mscsmentioning
confidence: 99%
“…To date, ADSCs have become excellent candidates for research and clinical applications. Many studies have shown that ADSC transplantation efficiently improved almost all symptoms of certain diseases, such as liver fibrosis (Harn et al, 2012), nerve defects (Gu et al, 2012;Liu et al, 2011;Santiago et al, 2009), ischemia (Mazo et al, 2012;Rigol et al, 2010), skeletal muscle injury (Pecanha et al, 2012), passive chronic immune thrombocytopenia (Xiao et al, 2012), and myocardial infarction (Yang et al, 2012) in animals, and systemic sclerosis in humans (Riordan et al, 2009;Scuderi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%